Design And Implementation Of An Artificial Neural Based Control System Network For A Move Master Robotic Arm - Gutiérrez Ramírez, Camilo Andrés; Beltrán García, Diego Felipe; Montoya Gómez, Jairo Orlando (Ingeniería Solidaria, 2010)
The project aims at fi nding an optimum displacement level with which, the fi ve degree of freedom, MoveMaster robot may move its joints when determining an appropriate trajectory to reach a specifi c point. To achieve this end we implemented a neural network based smart system that stores all the possible rotations done by the handler needed to reach a specifi c point, determining optimum movement while avoiding collision with the robot. A mathematical model was developed to obtain the equations that would identify the handler, and which will be used to train the neural network and the system’s control.